2013
DOI: 10.1111/cea.12089
|View full text |Cite
|
Sign up to set email alerts
|

Serum metabolomics reveals pathways and biomarkers associated with asthma pathogenesis

Abstract: These data showed that (1)H-NMR-based metabolite profiling of serum may be useful for the effective diagnosis of asthma and a further understanding of its pathogenesis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

12
150
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 145 publications
(176 citation statements)
references
References 40 publications
12
150
1
Order By: Relevance
“…Another study by Jung et al [22] profiled the serum of asthmatic patients using NMR and showed an increase in succinate; however, glutamine was also shown to be increased, which is opposite of our results. Nevertheless, the increased TCA-cycle metabolism may suggest an enhanced requirement for energy due to the greater effort required to breathe during exacerbation and most likely is a response to hypoxic stress due to poor oxygenation.…”
Section: Discussioncontrasting
confidence: 99%
See 2 more Smart Citations
“…Another study by Jung et al [22] profiled the serum of asthmatic patients using NMR and showed an increase in succinate; however, glutamine was also shown to be increased, which is opposite of our results. Nevertheless, the increased TCA-cycle metabolism may suggest an enhanced requirement for energy due to the greater effort required to breathe during exacerbation and most likely is a response to hypoxic stress due to poor oxygenation.…”
Section: Discussioncontrasting
confidence: 99%
“…The TCA cycle is a series of enzymatic reactions that are used by aerobic organisms to generate energy and involves the oxidation of acetate derived from carbohydrates, fats or proteins. Succinate is an intermediate in this cycle and is greatly enriched in the asthma samples; this finding was consistent with previous reports of changes in the urine [8] or serum [22] of asthmatic patients by NMR-based metabolomics analysis. The study by Saude et al [8] showed that five metabolites acting in the TCA cycle (succinate, fumarate, oxaloacetate, cis-aconitate and 2 -oxoglutarate) were present at higher abundances in urine in asthmatic patients who had recently suffered an exacerbation.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Metabolomics refers to the global investigation of metabolites in biological systems (comparing normal to disease) (Xu et al 2014), and has been applied to allergic asthma to profile metabolic changes and identify disease biomarkers (Lara et al 2008;Ho et al 2013Ho et al , 2014bSaude et al 2009Saude et al , 2011Mattarucchi et al 2012;Jung et al 2013). We have recently uncovered novel disease-relevant metabolic changes in the bronchoalveolar lavage fluid (BALF) from experimental mouse asthma, which involved major losses of sugars with resultant increases in energy metabolites and reductions of sterols (Ho et al , 2014b.…”
Section: Introductionmentioning
confidence: 99%
“…The endotype of high F E NO asthmatics showed a higher level of taurocholate than that of low F E NO asthmatics [19]. A few serum metabolites, including choline and arginine, showed positive correlations with FEV 1 % values [20]. However, most metabolites to date are neither directly related to the pathogenesis of asthma nor easy to measure repeatedly in clinical practice.…”
Section: Discussionmentioning
confidence: 93%